VR4DT: Virtual Reality for Driving Test - Swarnkar, Nishant; Singh Chug, Inderpal; Bagwan, Faraz; Thorat, Gaurav (International Journal of Computer Sciences and Engineering, 2025)
In this paper the virtual reality augmented R.T.O. testing with an interactive virtual environment is presented. It was designed as a modular system that can convert a car using Google Cardboard to in virtual reality (VR) car. Novel hardware components embedded with sensors were implemented on stationary car to monitor driver performance while immersing them in a virtual reality driving simulator providing to driver with visual and hepatic feedback.